2015
DOI: 10.1542/peds.2014-1073
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose and Warmth for Analgesia in Healthy Newborns: An RCT

Abstract: BACKGROUND AND OBJECTIVE: Increasing data suggest that neonatal pain has long-term consequences. Nonpharmacologic techniques (sucrose taste, pacifier suckling, breastfeeding) are effective and now widely used to combat minor neonatal pain. This study examined the analgesic effect of sucrose combined with radiant warmth compared with the taste of sucrose alone during a painful procedure in healthy full-term newborns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 50 publications
(32 reference statements)
0
8
0
1
Order By: Relevance
“…The remaining 82,234 references were reviewed by 2 of the authors (V.S., A.T.) against the inclusion criteria. 9 Five studies were excluded after reviewing the full manuscript as it included: (1) combined interventions versus control (n=1) 17 ; (2) a no comparator group (n=2), 18 , 19 ; (3) did not include intervention according to the clinical question (n=1) 20 ; and (4) the procedure was SC injection of normal saline (n=1). 21…”
Section: Resultsmentioning
confidence: 99%
“…The remaining 82,234 references were reviewed by 2 of the authors (V.S., A.T.) against the inclusion criteria. 9 Five studies were excluded after reviewing the full manuscript as it included: (1) combined interventions versus control (n=1) 17 ; (2) a no comparator group (n=2), 18 , 19 ; (3) did not include intervention according to the clinical question (n=1) 20 ; and (4) the procedure was SC injection of normal saline (n=1). 21…”
Section: Resultsmentioning
confidence: 99%
“…Their results showed that the sucrose plus warmer group cried and grimaced for 50% less time after the vaccination than the sucrose alone group and they also showed less physiological response to pain. 7 Many such studies have proved that oral dextrose (different concentrations have been used in different studies) reduced the crying time of infants experiencing procedural pain. [8][9][10][11] The other methods commonly used for management of pain include expressed breast milk, non-nutritive sucking or oral sucrose.…”
Section: Discussionmentioning
confidence: 99%
“…In Cochrane review done by Steven et al in July 2015, 14 it was concluded that sucrose is effective in reducing procedural pain in neonates without any serious side effects.…”
Section: Introductionmentioning
confidence: 99%